eval_uasi Penggunaan Antibiotik Profilaksis pada Pasien Bedah Caesar dengan Menggunakan Metode Gyssens di Rumah Sakit X Mojokerto - Amanda, Cantika Putri (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
Introduction: Delivery is a physiological process of expelling the fetus and placenta from the uterus, either spontaneously through the vagina or through operative procedures such as cesarean section. Cesarean section has become one of the commonly performed methods of delivery, but it carries a higher risk of surgical wound infections compared to normal delivery. The use of prophylactic antibiotics is important to prevent such complications; however, in practice, it often does not conform to guidelines, which can reduce the effectiveness of infection prevention and trigger antibiotic resistance. Objective: To assess the rationality of prophylactic antibiotic use in cesarean section patients at Hospital X in Mojokerto. Method: This study employs a descriptive observational method with a retrospective approach. Data was collected from 87 medical records of cesarean section patients during the period of 2024–2025. The eval_uation of prophylactic antibiotic use was conducted based on the Gyssens method to assess the accuracy of diagnosis, indications, drug selection, dosage, route and interval of administration, as well as the duration of therapy. Results: The majority of patients (92%) received prophylactic antibiotics rationally (Gyssens category 0). A small number of patients fall into category IIa (5%) due to dose inaccuracies, and category IVd (3%) with the use of broad-spectrum antibiotics. Conclusion: The use of prophylactic antibiotics in cesarean section patients at Hospital X Mojokerto is mostly rational (92%), while (8%) is irrational.